PENGARUH TERAPI BERMAIN ASSOSIATIF TERHADAP KEMAMPUAN INTERAKSI SOSIAL PADA ANAK AUTIS - Matilda Martha Paseno; Yunita Gabriela Madu; Fransisco Irwandy; Anjelin Kristin Nikolas; Anjeli Parumpa (Media Keperawatan:Politeknik Kesehatan Makassar, 2022)
Introduction: The social interaction ability of autistic children is a disorder in children's development such as impaired social interaction, lack of eye contact, likes to be alone, unable to understand the rules in a social environment and hyperactivity.Aim To determine the effect of associative play therapy on the ability of social interaction in autism child.Method:This type of research uses a pre-experimental design with a one-group pretest–posttest design approach. Sampling in this study was carried out using a non-probability sampling method with a total sampling technique. The sample in this study were children with autism in SLBN 1 Bantaeng with a total of 30 respondents. This research instrument uses an observation sheet to measure the interaction ability of children and data analysis used a paired-sample t test with a significan p value of 0.005.Result : The is an influence of Associative Play Therapy with the Interaction Level of Autism Children with p value 0,000 < 0.005 then the hypothesis Hα is accepted and Hₒ is rejected.The conclusion of this study is that associative play therapy using plasticine can improve the social interaction skills of autism children.Recomendation The results of this study are expected to be able to expand knowledge and become a reference for researchers who want to use associative play therapy (plasticine) to improve social interactions of autistic children. Further researchers are also expected to examine the communication skills of autistic children.Keywords : Autism, Social Interaction Ability, Associative Play Therapy